The influence of media on the formation of civic culture of student youth - Olha Kafarska (Vasyl Stefanyk Precarpathian National University, 2017)
The article highlights the impact of the influence of media on the formation of civic cultureof students. Proved that the only harmonious cooperation of the state, parents, teachers and themedia provide the high level of civic culture of the young generation. Key words: civic culture, media, internet, college students.